Airways in cystic fibrosis are acidified: detection by exhaled breath condensate. Issue 11 (1st November 2002) - Tate, S; MacGregor, G; Davis, M; Innes, J A; Greening, A P
Abstract : Background: The loss of cystic fibrosis transmembrane conductance regulator (CFTR) mediated chloride conductance does not fully explain the diverse pathologies evident in patients with cystic fibrosis (CF). Bicarbonate (HCO3 − ) secretion is also impaired in CFTR expressing tissues and CFTR is thought to regulate HCO3 − secretion at the apical membrane of epithelial cells. We hypothesised that the epithelial lining fluid (ELF) of patients with CF would be acidified and that this may be worsened during an infective exacerbation due to the increased inflammatory burden. Methods: pH and nitrite levels in exhaled breath condensate (EBC) from 12 healthy non-smoking controls and 30 patients with CF (11 of whom were in an infective exacerbation) were measured. A further nine patients were studied before and after intravenous antibiotic treatment for an exacerbation of CF. Results: The pH of EBC was significantly lower in patients with stable CF than in controls (5.88 (0.32) v 6.15 (0.16), p=0.017), and was further reduced in CF patients with an exacerbation (5.32 (0.38), p=0.001) compared with stable CF patients. EBC pH increased significantly following antibiotic treatment from 5.27 (0.42) to 5.71 (0.42), p=0.049). Nitrite levels in EBC were increased in CF patients with an exacerbation compared with control subjects (4.4 (4.0) μm v 1.6 (1.6) μm p=0.047). No correlation was found between EBC pH and nitrite levels. Conclusions: These findings support the hypothesis that airway acidification occurs in CF. This acidity is in part a function of inflammation as the pH of the EBC of patients increased significantly with treatment of an exacerbation, although not to control levels. Acidic pH of the ELF may play a role in the pathophysiology of CF lung disease and requires further investigation.